Probability of default models of Russian banks - Anatoly Peresetsky; Alexandr Karminsky; Sergei Golovan (Bank of Finland, Institute for Economies in Transition (BOFIT), 2004)
This paper presents results from an econometric analysis of Russian bank defaults during the period 1997 2003, focusing on the extent to which publicly available information from quarterly bank balance sheets is useful in predicting future defaults.Binary choice models are estimated to construct the probability of default model. We find that preliminary expert clustering or automatic clustering improves the predictive power of the models and incorporation of macrovariables into the models is useful.Heuristic criteria are suggested to help compare model performance from the perspectives of investors or banks supervision authorities.Russian banking system trends after the crisis 1998 are analyzed with rolling regressions.
URN:NBN:fi:bof-201408072156
Keywords: 330; banks; Russia; probability of default model; early warning systems